Proposed user interface design criteria for children with dyslexia - Ullah Khan, Rehman; Bee Oon, Yin; Inam UlHaq, Muhammad; Hajarah, Siti (International Journal of Engineering and Technology, 2019)
Children with dyslexia have difficulties with accurate word recognition, poor spelling and inability to differentiate certain phoneme and colours. Writing is another issue that is faced by most kids with dyslexia. There are many font families, text colour contrast and input methods for interface designing such as word selection, dropdown list and typing from a keyboard. There is a need to investigate, what font family, input method, and colour can ease children with dyslexia. Therefore, this study aims to explore and propose a suitable font, colour and input method for children with dyslexia. For this purpose, we have designed a mobile application having several user interfaces to test with a group of children with dyslexia. Comparison results was further concluded to be a set of recommendations for future interface design for them.Â Â Â